iHEADEase: innovative head immobilisation device for special care patients during dental procedures / Mohd Isyrafuddin Ismail … [et al.] - Ismail, Mohd Isyrafuddin; Suhardi, Syafiqah Aina; Jusoh @ Mohd Zaki, Nur ‘Athifah; Yusof, Karimah; Kamaruddin, Azwin Assilah; Ahmad, Mas Suryalis (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Protective stabilisation using mechanical restraint is a dental behavior technique designed to optimise patient comfort and safety during dental procedures. By facilitating proper patient positioning, it contributes to a more positive experience while minimising potential risks for both patients and the dental team. Dental professionals often encounter challenges when performing dental examinations and treatments on special care patients due to involuntary or voluntary head movements for example in patient with cerebral palsy. Traditional mechanical restraints are typically rigid, lack flexibility, and are difficult to adjust. These limitations are particularly pronounced when managing uncooperative patients or individuals receiving dental care at home, where flexibility and portability are essential. The objective of this project is to develop a portable head immobilization device for special care patients undergoing dental treatment. The iHeadEase device features distinctive elements, including a customizable sponge that conforms to the patient's facial contours, a Velcro strap that can be adjusted to fit every user, and built-in portable speakers for distraction purposes. A neck pillow provides support and limits head movement, promoting enhanced comfort throughout the procedure. iHeadEase ensures a well-distributed force on the patient's head, thereby enhancing overall procedural safety, comfort, and efficiency for both the patient and the dental team. Due to its universal design, it is suitable to be used by dentists and caregivers worldwide.